A Survey of Factors Influencing Drug Choice and the Prescribing Attitudes Among Junior Doctors of Two Major Tertiary Care Hospitals in Chittagong City (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: The magnitude of rational prescribing is well known but the irrationalities and errors in prescriptions are seen worldwide as the training of future doctors is still not up to the mark. This study aimed to find out the factors influencing drug choice and the prescribing attitudes among junior doctors of two major tertiary care hospitals in Chittagong city.Methods: A cross-sectional questionnaire survey was conducted among the junior doctors of Chittagong Medical College Hospital (CMCH) and Chattagram Maa -O- Shishu Hospital Medical College (CMOSHMC) to assess the factors influencing drug choice and the prescribing attitudes among junior doctors during August 2016.Results: The questionnaires were provided to 220 participants of whom 162 (73.63%) participants provided a complete response to the survey. The response rate was 75.89% in CMOSHMCH and 71.29% in CMCH. The majority (87.03%) of junior doctors mentioned that they are highly influenced by their supervising senior doctors’ patterns of prescriptions. About 79.01% of them took the cost of drugs into consideration while prescribing. 58.64% of the prescribers reported their confidence while prescribing without supervision. On the otherhand, 33.33% doctors mentioned that side effects of the drug changed their patterns of prescriptions. Only one-third (33.95%) of the junior doctors opined that the pharmaceutical promotional offers never influence them.Conclusion: Junior doctors decide their drug of choice mainly by copying their supervising senior doctors’ prescriptions without knowing how to choose, and they feel less confident while prescribing. Issues of drug cost, adverse drug reactions concerned the majority of the participants, but they do not have the clear ideas on how to deal with these practice behaviours. Moreover, pharmaceutical promotional offers significantly persuaded the junior doctors’ prescription patterns. So, there is a need for the continuous medical education programs in hospital settings to train the junior doctors for building capacities and competencies while prescribing.Chatt Maa Shi Hosp Med Coll J; Vol.17 (1); Jan 2018; Page 17-22